Prognostic value of the lactate-albumin ratio in trauma: A comparison with shock index and injury severity score - Jonghan Park; Wook Tae Yang; Seok-Ran Yeom; Sung-Wook Park; Young Mo Cho; Won Ung Tae; Hyuk Jin Choi; Mahnjeong Ha; Seunghan Yu; Up Huh; Dongman Ryu; Chanhee Song; et al. (PLoS ONE, 2025)
This study aimed to assess the predictive value of lactate-to-albumin ratio (LAR) for in-hospital mortality and massive transfusion (MT) in severe trauma cases. This retrospective, observational, single-center study included patients who presented to a trauma center between 2016 and 2022. The primary outcome was in-hospital mortality, and the secondary outcome was MT. Logistic regression analysis was performed to determine whether LAR was an independent risk factor. The area under the receiver operating characteristic (AUROC) curve was calculated to evaluate the predictive value of LAR. In total, 5,304 patients were included. Logistic regression analysis identified LAR as an independent risk factor for in-hospital mortality. The AUROCs for predicting in-hospital mortality using LAR, Injury Severity Score (ISS), and Shock Index (SI) were 0.74 (95% confidence interval [CI], 0.73–0.75), 0.78 (95% CI, 0.77–0.779), and 0.51 (95% CI, 0.49–0.52), respectively. LAR was statistically significant compared with SI (p < 0.0001; 95% CI, 0.194–0.276) and similar to ISS (p = 0.0039; 95% CI, 0.0115–0.0604). LAR (0.84; 95% CI, 0.83–0.85) demonstrated superior predictive power for MT compared with SI (0.68; 95% CI, 0.67–0.70) and ISS (0.79; 95% CI, 0.78–0.80). LAR demonstrates a superior predictive ability for in-hospital mortality and MT.